A non-invasive nanobody probe for high precision mapping of Lck spatial distribution - Tyritidis, Ioannis; Tsioupros, Evangelos; Christou, Pantelis; Koutras, Nikolaos; Morfos, Vasileios; Nika, Konstantina (Frontiers in Immunology, 2024)
The tyrosine kinase Lck is mandatory for initiating signaling responses downstream the antigenic T cell receptor (TCR). Numerous studies have shown that a prerequisite for efficient and well-balanced Lck regulation and function is its finely orchestrated spatial distribution pattern, especially at the plane of the plasma membrane. There is a wealth of knowledge on Lck localization sites, preference for specialized lipid microenvironments and colocalization partners. However, several questions concerning the spatial organization of its differentially phosphorylated conformers and the dynamics of their juxtaposition in relation to ligated and non-ligated TCRs remain elusive. In this brief report we introduce a non-invasive nanobody-based approach for mapping Lck subcellular allocation with high precision. Our initial data using this methodology, provide insight into the topology of Lck in resting T cells and its confined localization in a strictly delimited environment within the plane of the plasma membrane.